2022
DOI: 10.1002/vms3.761
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and antimicrobial resistance of Enterococcus faecalis isolated from seafood samples

Abstract: Background: Enterococcus faecalis is considered an opportunistic foodborne pathogen.The present study aimed to assess the prevalence, antimicrobial resistance, virulence characters, and molecular typing of E. faecalis strains isolated from seafood samples. Methods: Two hundred and seventy-six seafood samples were collected. E. faecalis was isolated from samples using bacterial culture. Furthermore, the disk diffusion assessed their antimicrobial resistance. Also, the distribution of virulence factors was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…All isolates from wild fish were susceptible to fosfomycin, a reserve group of antibiotics. Some previously reported studies from Bangladesh, Ghana, and the Persian Gulf also found similar results for these antibiotics [23][24][25]. In this study, in general, we found that E. faecalis strains from cultured fish showed higher levels of antibiotic resistance than those from wild fish, possibly due to the pressure of selective antibiotic uses in fish firms.…”
Section: Antibiotic Resistance Patternsupporting
confidence: 85%
See 1 more Smart Citation
“…All isolates from wild fish were susceptible to fosfomycin, a reserve group of antibiotics. Some previously reported studies from Bangladesh, Ghana, and the Persian Gulf also found similar results for these antibiotics [23][24][25]. In this study, in general, we found that E. faecalis strains from cultured fish showed higher levels of antibiotic resistance than those from wild fish, possibly due to the pressure of selective antibiotic uses in fish firms.…”
Section: Antibiotic Resistance Patternsupporting
confidence: 85%
“…Another study by Petersen and Dalsgaard [ 20 ] reported a 69% presence of E. faecalis in fish intestines from an integrated and traditional fish firm in Thailand. However, a recent study by Noroozi et al [ 21 ] found a lower % prevalence of E. faecalis in fish, of 30%. In another study, Hassan et al [ 22 ] isolated samples from cultured Oreochromis niloticus and Mugil cephalus in Egypt and found a lower prevalence of E. faecalis (50.50%) than ours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it posed a serious risk to the patients receiving treatment. Clinical samples of Enterococcus species revealed resistance to ampicillin of 80%, gentamycin of 60%, doxycycline of 73.3%, and vancomycin of 6.7% in Ethiopia [26]. According to the study from the northern region of India [27], no isolates of Enterococcus species were found to be resistant to the antibiotics vancomycin and high levels of gentamycin and streptomycin were both effective against Enterococcus species.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm-forming bacteria possess several advantages over single planktonic cells, such as enhanced resilience against environmental stress conditions, sanitizers, and antimicrobial agents ( 2 ). Moreover, E. faecalis strains with high virulence and resistance are thought to be found in seafood samples ( 3 ). E. faecalis is one of the primary triggers of hospital-acquired infections and can cause serious infections, including meningitis, bacteremia, urinary tract infections, gastrointestinal infections, periodontitis, and others ( 4 ).…”
Section: Announcementmentioning
confidence: 99%